Double core-hole states in SiX4 (X = F, Cl, Br, and CH3) molecules derived by photoelectron and KLL Auger spectroscopy. (August 2015) - Püttner, R; Marchenko, T; Guillemin, R; Journel, L; Goldsztejn, G; Rueff, J-P; Céolin, D; Lindle, D W; Lago, A; Ueda, K; Takahashi, O; Piancastelli, M N; et al.
Synopsis: In recent years double core-hole states are intensively studied since their chemical shifts provide detailed information about initial-state and relaxation effects in a molecule. We derived the Si 1 s −1, 2 s −1, and 2 p −1 binding energies as well as the Si 2 s −2, 2 s −1, 2 p −1, and 2 p −2 double-core hole binding energies of different SiX4 systems in order to derive the chemical shifts. Based on these results we created Wagner plots, which give insight in the initial state and the relaxation effects in the different molecules.